The Effect of Public Accounting Firm Size, Profitability, and Solvencey on Audit Delay in Indonesia’s Infrastructure Sector - Alfrida, Santika; Yuniarti, Evi; Mareta, Fitri (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This study aims to analyze the effect og public accounting firm (PAF) size, profitability, and solvency on audit delay in infrastructure companies listed on the Indonesia Stock Exchange (IDX) during teh 2021-2024 period. Methodology/approach: The research uses quantitative methods with secondary data derived from audited annual reports of 20 infrastructure companies listed on the IDX. The samplewas selected using purposive sampling technique. Audit delay is measured as the number of days between the fiscal year-end and the date of the independent auditor’s report. The independent variabels are PAF size (dummy variable), profitability (ROA), and solvency (DAR). Data analysis was conducted using multiple liniear resression with SPSS. Results/findings: The results indicate that PAF size has no significant effect on audit delay, profitability has a positive effect on audit delay, and solvency significantly affect audit delay. Conclusions: The findings highlight that audit delay in infrastructure companies is influenced more by profitability and solvency rather than PAF size. Higher profitability tends to increase audit delay due to the complexity of financial transactions, while higher solvency reduces audit delay since companies with better financial structure are easier to audit Limitations: This study only focuses on infrastructure companies for the 2021-2024 period and uses limited financial ratios as proxies. Contribution: This study adds evidence on audit delay in the infrastructure sector and provides insights for investors, regulators, and management to assess the timeliness of financial reporting.